2019
DOI: 10.1002/mame.201900213
|View full text |Cite
|
Sign up to set email alerts
|

Two in One: Modified Polyurethane Foams by Dip‐Coating of Halloysite Nanotubes with Acceptable Flame Retardancy and Absorbency

Abstract: Poor flame retardancy of polyurethane foam (PUF) limits its practical application in many fields. Here, flame‐retardant performance of PUF is improved by a simple dip‐coating method. Halloysite nanotube (HNT) coating can be uniformly bonded to PUF surfaces via hydrogen‐bonding interactions, which is confirmed by element mapping and X‐ray photoelectron spectra. Density and mechanical properties of PUF increase with the concentration of HNT suspension, while porosity of the foam decreases with HNT loading. Weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…[13] Recently, halloysite nanotubes (HNT) as environmentally friendly nanofillers for enhancing the flame-retardant performance of polymer composites has received increasing attention. [14][15][16][17][18] HNT is a hydrated polymorph of 1:1 rolling phyllosilicate clay with a chemical formula of Al 2 Si 2 O 5 (OH) 4 ÁnH 2 O, which is the kaolin group. [19] These biocompatible and naturally abundant tubular nanomaterials have an external diameter of 50 nm to 80 nm, internal lumen of 10-50 nm, and length of approximately 1,000 nm.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Recently, halloysite nanotubes (HNT) as environmentally friendly nanofillers for enhancing the flame-retardant performance of polymer composites has received increasing attention. [14][15][16][17][18] HNT is a hydrated polymorph of 1:1 rolling phyllosilicate clay with a chemical formula of Al 2 Si 2 O 5 (OH) 4 ÁnH 2 O, which is the kaolin group. [19] These biocompatible and naturally abundant tubular nanomaterials have an external diameter of 50 nm to 80 nm, internal lumen of 10-50 nm, and length of approximately 1,000 nm.…”
Section: Introductionmentioning
confidence: 99%
“…It should be emphasized that squeezing the sponges during the immersion process is an effective way to enhance the loading. [ 40 ] The process was repeated five times to enhance the loading efficiency. The loaded samples were dried in an oven at 40°C for 12 h. The sustained release process was carried out as follows: the samples sealed with Dialysis bags (molecular mass cutoff: 1000 Da) were soaked in 300 ml deionized water at 37°C with a stirring speed of 100 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been reported that HNTs exhibit promising applications in the fields of biomaterials, catalysis, , reinforcement, energy, membrane, and purification. , The high L/D ratio has been demonstrated to be favorable to improve the tensile strength when embedded into a polymeric matrix . Significantly, the hollow structure makes HNTs desirable thermal barriers in the flame-retardant field. , Therefore, the functionalization of fibers by HNTs may be an effective approach to lower fire hazards. The hydroxyl groups distributed over the surface of HNTs can participate in condensation reactions, which can be chemically modified with a silane coupling agent, catechol, arylboronic acid, etc.…”
Section: Introductionmentioning
confidence: 99%